A Case Study of Health-Related Support Processes in 2 Happy, Gay Couples. Issue 6 (November 2018) - Novak, Josh R.; Gast, Julie; Peak, Terry; Johnson, Rhees; Morrey, Rachel; Smith, Madeline; Souders, Marissa
The purpose of this case study was to explore 2, early-relationship, same-sex couples on the strategies used to support their partner's engagement in health promoting behaviors. A semistructured interview protocol was used to conduct 120-minute interviews with each couple and analyzed using grounded theory methods. Five organizing categories emerged during the analysis, resulting in a conceptual process model of health-related support in same-sex relationships. These categories, provided a snapshot of how processes interact with each other; they were context, relationship dynamics, health support processes, couple adaptation, and balancing physical/relational health. Couples described the balancing of relational and physical health as an ongoing, important theme in the success of health support. Implications for both health prevention and intervention are discussed.